Developing Auditor Competencies through Continuous Training and Education - Rumasukun, Mohammad Ridwan (Golden Ratio of Auditing Research, 2024)
This study examines the development of auditor competencies through continuous training and education, focusing on the integration of digital literacy and emotional intelligence into training programs. It employs a synthesis of literature from diverse perspectives to explore theoretical and managerial implications. Theoretical implications highlight the need to expand traditional notions of auditor competence to include soft skills and behavioral competencies, emphasizing the importance of emotional intelligence in auditor-client relationships and digital literacy in navigating digital audit environments. Organizational factors influencing competency development are also identified, with a focus on the role of leadership styles, organizational culture, and learning climate. Managerial implications suggest the recalibration of training programs to prioritize holistic competency development, including digital literacy and emotional intelligence. Organizational leaders are urged to champion digital transformation initiatives and foster a culture of continuous learning and innovation. Mentorship programs and communities of practice are proposed as means to facilitate knowledge sharing and professional development. Overall, this study provides insights for both theoretical understanding and managerial practice in enhancing auditor competencies to meet the challenges of the contemporary business environment.